Pengembangan Media Pembelajaran Video Animasi Menggunakan Aplikasi Capcut pada Pelajaran IPAS Kelas V SDN 15 Koto Besar - Asmaryad, Ahmad Ilhami; Darniyanti, Yulia; Afrilia, Dina (Jurnal Ilmiah Dikdaya, 2024)
This research is based on the lack of interest of students in participating in learning of students who are fashionablewhen given questions by teachers and have not used media that attract students' attention in learning, this research has acompliment, namely to produce video animation learning media for science subjects class V SDN 15 Koto Besar that is valid,practical and effective. The type of research used is R&D (Research and Development), or development research, with theADDIE model, (Analysis, Design, Development, Implementation, and Evaluation). There are several stages of development, first,analysis, including analysis of needs, characteristics of students and curriculum, and second, the design of animation videopreparation. Third, the development was carried out a validation test of the animation video. The fourth implementation iscarried out by practicality test and finally evaluation in the feasibility test of animated video products. This development researchobtained the results of a validation test by three expert validators with an average score of 78% of the very valid category, apracticality test conducted by a class V homeroom teacher with an average score of 90% of the very practical category. Theresults of the trial were seen from the student response questionnaire obtaining an average score of 88.6%. Based on the resultsobtained, it can be concluded that the animated video in the science and science subject in the independent curriculum of grade VSDN 15 Koto Besar, is valid and practical.